Գևորգ Կաղի ժամանակաշրջանի ճշգրտման փորձ - Թերզյան, Գայանե
Gevorg Kagh is known from several manuscripts of the Mashtots Matenadaran аs the author of a “cause” and a commentary on the Pauline epistles, an abridged version of John Chrysostom’s work of the same title. Little is known about his life and work. Gevorg Kagh’s name is first mentioned in the correspondences of the 11th century intellectual Grigor Magistros. Gevorg Kagh is the addressee of two of his letters, evidencing that he lived in the 11th and not in the 12th century, as has been postulated. He was one of the most renowned scholars and vardapets of his time and cultivated a close relationship with Grigor Magistros. Геворг Каг известен по нескольким рукописям Матенадарана им. Месропа Маштоца как автор толкования посланий апостола Павла и “причин” (вводных статей) к ним. О его личности и деятельности мало что известно. Первое упоминание его имени мы встречаем в посланиях известного деятеля XI века Григора Магистроса. Георг Каг –адресат двух его писем, из которых становится ясно, что он жил не в XII, как предполагают некоторые, а в XI веке. Он был одним из известных ученых вардапетов своего времени и находился в тесных отношениях с Григором Магистросом. Под именем Геворга Кага до нас дошли “причины” посланий апостола Павла, ему же приписывают толкование четырнадцати посланий апостола, представляющее сокращенный вариант одноименного толкования Иоанна Златоуста.
Keywords: Բանասիրություն